2012
DOI: 10.1099/mic.0.055970-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of antibacterial compounds of Pseudoalteromonas flavipulchra JG1

Abstract: Pseudoalteromonas flavipulchra JG1 produces a protein PfaP and a range of small-molecule compounds with inhibitory activities against Vibrio anguillarum. The PfaP protein was purified from the extracellular products of JG1 by electroelution, and antibacterial activity was observed by an in-gel antibacterial assay. The complete amino acid sequence (694 aa) of PfaP was determined by de novo peptide sequencing and subsequent alignment with the proteome sequence of strain JG1. The calculated molecular mass of PfaP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…This mainly attributes to more genes involved in ABC-type antimicrobial peptide transport system (COG0577, COG1136), beta-lactamase class C and other penicillin binding proteins (COG1680), cation/multidrug efflux pump (COG0841), ABC-type siderophore export system (COG 4615) and those related to the synthesis of potential bioactive compounds, such as nonribosomal peptide synthetase (NRPS) modules (COG1020) and polyketide synthases (COG 3321). The abundance of genes involved in expression and transport of potential primary and secondary metabolites and defense compounds are consistent with the capability of P. flavipulchra to produce various antimicrobial compounds [10] and generate survival advantages in marine environments [8]. …”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…This mainly attributes to more genes involved in ABC-type antimicrobial peptide transport system (COG0577, COG1136), beta-lactamase class C and other penicillin binding proteins (COG1680), cation/multidrug efflux pump (COG0841), ABC-type siderophore export system (COG 4615) and those related to the synthesis of potential bioactive compounds, such as nonribosomal peptide synthetase (NRPS) modules (COG1020) and polyketide synthases (COG 3321). The abundance of genes involved in expression and transport of potential primary and secondary metabolites and defense compounds are consistent with the capability of P. flavipulchra to produce various antimicrobial compounds [10] and generate survival advantages in marine environments [8]. …”
Section: Resultsmentioning
confidence: 77%
“…General features of these genomes were given in Table  1 and their phylogenetic relationship based on the 16S rRNA gene (Figure  1) indicated that P. flavipulchra JG1 formed a cluster with P. tunicata D2. Comparing with other sequenced Pseudoalteromonas strains, P. tunicata D2 [12] also exhibited great inhibitory activities against several specific organisms as in P. flavipulchra JG1 [10], indicating that P. flavipulchra was functionally closely related to P. tunicata D2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 3a, 3h, 4a-j,7 and 8 were initially evaluated for their in vitro fungistatic activity against 13 Candida spp. clinical isolates including: C. albicans (8 isolates), C. tropicalis, C. glabrata, C. krusei (2 isolates), C. lusitaniae and 6 reference strains: C. albicans ATCC 10231, C. albicans ATCC 26790, C. kursei ATCC 6258, C. glabrata ATCC 2001, C. glabrata DSM 11226 and C. parapsilosis ATCC 22019.…”
mentioning
confidence: 99%
“…The marine antagonistic bacterium Pseudoalteromonas flavipulchra JG1, with a golden yellow color, was isolated from water used to rear healthy turbot (Scophthalmus maximus) in Qingdao, China (7). JG1 was confirmed to show excellent antibacterial activities against many fish pathogens and could synthesize a range of antibacterial compounds, including the protein PfaP and five small molecules (12). Due to these properties, JG1 and/or its products could be used as potential probiotics or antibiotics in aquaculture.…”
mentioning
confidence: 99%